Problematika Pembelajaran Biologi Urban dan Solusinya - Farhan Pratama; Lidya Banila; Indah Heriyanti Kartika Sari; Tri Isna Dayuwati; Ade Suryanda (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The purpose of this study was to find out the problems of learning urban biology and to explore the characteristics of learning urban biology at SMAN 1 Bojonggede. The research method used in this study is a case study which is qualitative research with a descriptive design, where the researcher conducts a detailed exploration of an event, process, activity of more or one person by means of interviews or observations with resource persons, with data collection techniques. in the form of interviews and observations of biology teachers at SMAN 1 Bojonggede in Bojong Gede District, Bogor Regency, West Java. The data analysis techniques used are 1) Data collection, 2) Data reduction, 3) Data presentation, 4) Data analysis, and 5) Conclusions. In the interview, the research team asked several questions to the informants, including 1) How is the process of biology learning activities in urban areas, 2) about literacy in urban areas, 3) about the practicum process carried out in urban schools, and 4) the use of the internet in urban areas. urban area. Most of the interviews that have been conducted on urban biology learning activities at SMAN 1 Bojonggede mostly use internet-related devices to support learning activities. The conclusion in this study is that the characteristics of urban biology learning activities at SMAN 1 Bojonggede use media related to the internet to support learning.